Soil-Water Characteristics of the Low Liquid Limit Silt considering Compaction and Freeze-Thaw Action - Yongsheng Yao; Shenping Luo; Junfeng Qian; Jue Li; Hongbin Xiao (Advances in Civil Engineering)
The soil-water characteristic curve of silty soil in seasonal frozen area during freezing-thawing process was studied in this study. By means of a laboratory test, specimens with different compaction degrees and different initial moisture content were prepared and put into the temperature change testing machine for freeze-thaw action. The influence of different degrees of compaction and different times of freeze-thaw action on SWCC of low liquid limit silt was analyzed, a V-G model was used to fit the test data, and a set of fitting parameters with a reference value was obtained. At the same time, the change of microstructure between soil particles during the freezing-thawing cycle is illustrated. The results showed that with the same water content and the same compactness, the matric suction of the test soil decreased with the increase of freeze-thaw cycles. For the same number of freeze-thaw cycles, the greater the compactness, the greater the matric suction of the soil. The V-G model can well represent the SWCC of low liquid limit silt during the freeze-thaw cycle.